Alvin Ho : allergic to girls, school, and other scary things - Look, Lenore; Pham, LeUyen (New York : Yearling, 2008)
A young boy in Concord, Massachusetts, who loves superheroes and comes from a long line of brave Chinese farmer-warriors, wants to make friends, but first he must overcome his fear of everything.
"A Yearling Book."
Keywords: Chinese Americans -- Fiction; Fear -- Fiction; Friendship -- Fiction; Self-confidence -- Fiction; Concord (Mass.) -- Fiction